2D‐structuring of glasses via thermal poling: A short review. (27th April 2017) - Lipovskii, Andrey; Zhurikhina, Valentina; Tagantsev, Dmitry
Abstract: Current status of studies devoted to thermal poling of multicomponent glasses and related applications are briefly reviewed. Physical phenomena occurring in the course of the poling manifest themselves in second harmonic generation (SHG), linear electrooptical effect, formation of surface and refractive index relief and changes of chemical properties of poled glasses. All these effects can be used for structuring of the glass surface and glass‐metal nanocomposites in the terms of chemical reactivity, SHG, formation of diffraction gratings, and growth of ordered metal nanoparticles. Both literary data and results of own researches of the authors are presented.